Sistema distribuído para alocação de recursos baseada em necessidades - Possani, Cleverton Marlon (2006)
Distributed architectures systems possesses an ample processing power when its resources work through cooperation, forming virtual organizations. The exploitation of idle geographically distributed resource is one of the objectives of the grid computation. In these environments, users application need a certan amount of resources to fill their execution necessities. At the same time, to find these resources, its necessary a way of expressing them. This work presents the development of an archetype to provide abilities of alocation resource to users application. Using for that informations about resources description and necessities. This necessities determine what kind of resource can be used in order to the application be executed with the help of the grid computation. A simulation environment was developed in order to evaluate the performance and to find some archetype critic points.